Financial and Ecological Evaluation of Hydrogen Production Processes on Large Scale1. Issue 6 (28th April 2016) - Machhammer, Otto; Bode, Andreas; Hormuth, Wolfgang
Abstract: Hydrogen is widely seen as energy carrier of the future. Different technologies are under development to produce hydrogen at competitive cost but with significantly reduced carbon footprint. Two conventional technologies, namely, methane steam reforming and coal gasification, are compared based on product cost and carbon footprint with four new technologies, i.e., metal‐oxide cycle, water electrolysis, biomass gasification, and methane pyrolysis. To evaluate the carbon footprint for methane pyrolysis, system extension and differential methods are applied. For the boundary conditions selected here, methane pyrolysis yields very good values for product cost and carbon footprint. Therefore, a cross industry technology development of methane pyrolysis was initiated. Abstract : Hydrogen plays an important role in many future scenarios. In this connection it is frequently assumed that this gas cannot only be obtained economically from regenerative sources, but also that its production will be for the most part climate‐friendly. Various production technologies are evaluated from these two points of view.